Analisis Miskonsepsi Pada Buku Ajar Biologi SMA Kelas XII - Agustina, Renny; Sipahutar, Herbert; Harahap, Fauziyah (Magister Pendidikan Biologi, Universitas Negeri Medan, 2016)
This research was emerged based on the facts about the presence of many conceptual problems that lead misconceptions in biology textbooks while teachers rely too much on textbooks as learning source in class. This study were aimed to analyze the misconceptions in the high school biology textbook for grade 12 which shall be used by high school students, grade 12 in the city of Binjai, especially for the subjects (growth and development, metabolism, heredity, evolution, and biotechnology) as well as to determine the percentage of misconceptions categories (misidentifications, overgeneralizations, oversimplification, obsolete concept and term, under generalizations). The research method used in this research is descriptive. The concepts contained in the textbook were analyzed by using analysis of documents or textbooks based on the criteria of each misconception categories contained in the instrument for misconceptions identification and then comparedto foreign textbooks. The results of this study showed that: (1) the percentage of misconceptions on the subject of (a) the growth and development (26,09%); (b) metabolism (26,09%); (c) heredity (26,09%); (d) evolution (8,69%); and (e) biotechnology (13,04%); (2) the percentage of misconceptions categories: (a) misidentifications (8,69%); (b) overgeneralizations (17,40%); (c) oversimplifications (69,56%); (d) obsolete concept and term (0,00%); (e) under generalizations (4,35%).